2011
DOI: 10.3846/16484142.2011.623824
|View full text |Cite
|
Sign up to set email alerts
|

Ethanol–biodiesel–diesel Blends as a Diesel Extender Option on Compression Ignition Engines

Abstract: Increasing fuel demand, decreasing natural reserves and environmental consciousness have together led to testing and implementing new fuels and blending components of compression ignition engines. Biofuels are very commonly added to fossil fuels, mostly ethanol to gasoline and FAME to diesel. Harmonizing their properties with engines is a great challenge for automotive and oil industry. Increasing demand for diesel oil in Europe raised the question about the possibility of increasing the amount of bio extender… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
19
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(23 citation statements)
references
References 11 publications
3
19
0
1
Order By: Relevance
“…29,30 vibrations are increased per unit of time, thereby causing more noise pollution. This finding was consistent with the results of studies conducted by Taghi Zadeh-Ali Aaraei et al 34 and Zoldy 35 (see Figure 6). In Figure 6, it is shown that a change in the percentage of bioethanol in fuel mixtures on average led to little change in noise pollution at various revolutions, whereas the noise pollution emitted in the third gear was more than that in the second gear.…”
Section: Resultssupporting
confidence: 93%
“…29,30 vibrations are increased per unit of time, thereby causing more noise pollution. This finding was consistent with the results of studies conducted by Taghi Zadeh-Ali Aaraei et al 34 and Zoldy 35 (see Figure 6). In Figure 6, it is shown that a change in the percentage of bioethanol in fuel mixtures on average led to little change in noise pollution at various revolutions, whereas the noise pollution emitted in the third gear was more than that in the second gear.…”
Section: Resultssupporting
confidence: 93%
“…Therefore, biodiesel fuel was used to compensate the decrease in the aforesaid two properties [16]. The impact of biodiesel fuel on the CN of ethanol-diesel blends was predicted using the formula suggested in [46]. The CN of pure diesel fuel (CN D ) was predicted using the formula suggested in [47], as follows:…”
Section: Cetane Number and Viscositymentioning
confidence: 99%
“…In these, the biodiesel helps blend ethanol with diesel as it acts as an emulsifier. Results of numerous investigations, [13][14][15][16] showed that the bioethanol-biodiesel-diesel blends fulfil the cetane number, viscosity and lubricity requirements for standard diesel. The practical measurement, the engine bench tests showed that utilization of the new fuel decreases the emissions of the engine.…”
Section: Introductionmentioning
confidence: 99%
“…The brake-specific fuel consumption increases with the addition of alcohol. Alcohol fuels contain oxygen, so this will improve combustion, but power decreases due to lower calorific value compared with diesel, so using alcohol in large quantities is not favorable [13].…”
Section: Introductionmentioning
confidence: 99%